2019
DOI: 10.1371/journal.pntd.0007483
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic role of a research university and international partnerships in building research capacity in Peru: A bibliometric analysis

Abstract: Objective In Peru, the past three decades have witnessed impressive growth in biomedical research catalyzed from a single research university and its investigators who secured international partnerships and funding. We conducted a bibliometric analysis of publications by Peruvian authors to understand the roots of this growth and the spread of research networks within the country. Methods For 1997–2016, publications from Web of Science with at least one author affiliate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 27 publications
0
11
0
8
Order By: Relevance
“…For instance, UPCH and SES excel yearly supporting the conferences as members of the planning committee and their contribution can also be observed in the presence of their international collaborators; principally the London School of Hygiene and Tropical Medicine, Imperial College London, and Harvard University [10] . A recent study suggested that sustained, long-standing international partnerships promoted and built research capacity in Peru [13] . The annual number of publications increased 9-fold in a 20-year period characterized by the securement of partnerships and TB was among the main research areas that benefited during the seven-year period [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, UPCH and SES excel yearly supporting the conferences as members of the planning committee and their contribution can also be observed in the presence of their international collaborators; principally the London School of Hygiene and Tropical Medicine, Imperial College London, and Harvard University [10] . A recent study suggested that sustained, long-standing international partnerships promoted and built research capacity in Peru [13] . The annual number of publications increased 9-fold in a 20-year period characterized by the securement of partnerships and TB was among the main research areas that benefited during the seven-year period [13] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that sustained, long-standing international partnerships promoted and built research capacity in Peru [13] . The annual number of publications increased 9-fold in a 20-year period characterized by the securement of partnerships and TB was among the main research areas that benefited during the seven-year period [13] . The partnerships have greatly served the TB-affected population.…”
Section: Discussionmentioning
confidence: 99%
“…In Peru, the past three decades have witnessed impressive growth in biomedical research catalyzed from efforts made among local educational institutions and NIH securing international partnerships and funding through research training programs [ 11 ]. As a result, Peruvian physician-scientists have built and sustained longstanding international partnerships with funding accelerating quality research on diseases of local importance.…”
Section: Advocating For More Opportunities To Enhance Global Oral Heamentioning
confidence: 99%
“…A decolonial perspective, of research cooperation, however, is contested by bibliometric research of research networks that mostly coincide on highlighting the worldwide benefits of international scientific networks without considering possible the enduring heritage of colonial imbalances. Belter et al (2019) show an exponential number of publications on biomedical research due to the collaboration with researchers from the United States, the United Kingdom, Brazil, and Spain but criticize that research is mostly based on a single private university and the lack of long-term sustainability perspective of governmental funds. Based on citation impact measures, Aldieri et al (2018) argue that European universities improve the quality of their research reflected through collaboration but that Italian and Russian universities have benefited less than Germany, France, and the United Kingdom.…”
Section: Decolonial and Bibliometric Perspectives Of Research Cooperamentioning
confidence: 99%
“…To what extent does current scientific collaboration act as a form of neocolonial control that is exerted through knowledge production? Most studies on research partnerships (Baud, 2002; Mazzoleni & Nelson, 2007) and contemporary bibliometric analysis of research partnerships (Aldieri et al, 2018; Belter et al, 2019; Eduan & Yuanqun, 2018; Owusu-Nimo & Boshoff, 2017; Payumo et al, 2019; Pohl & Lane, 2018) seem to take for granted the positive outcomes of research collaboration for all parties through identifying social and educational conditions that enable scientific networks. Reflections on potential power relationships inherited from colonial legacies, however, are usually absent in this literature.…”
Section: Introductionmentioning
confidence: 99%